2021
DOI: 10.1016/j.ejmp.2020.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric response of a glass dosimeter in proton beams: LET-dependence and correction factor

Abstract: A radiophotoluminescent glass dosimeter (RGD) is widely used in postal audit system for photon beams in Japan. However, proton dosimetry in RGDs is scarcely used owing to a lack of clarity in their response to beam quality. In this study, we investigated RGD response to beam quality for establishing a suitable linear energy transfer (LET)-corrected dosimetry protocol in a therapeutic proton beam.The RGD response was compared with ionization chamber measurement for a 100-225 MeV passive proton beam. LET of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…Because of the LET dependence of RGD, we observed a 15.2% under‐response compared with the IC dose. The LET dependence of the therapeutic proton beam was consistent with our previous study using a passive system 13 . We obtained knormalLETnormalRGDnormalLET=0.035normalLET+1.090 from the linear fit between the RGD response and LET.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Because of the LET dependence of RGD, we observed a 15.2% under‐response compared with the IC dose. The LET dependence of the therapeutic proton beam was consistent with our previous study using a passive system 13 . We obtained knormalLETnormalRGDnormalLET=0.035normalLET+1.090 from the linear fit between the RGD response and LET.…”
Section: Discussionsupporting
confidence: 89%
“…14 In our previous study, we established that LET changes depending on the irradiation conditions, specifically for low-energy proton beams, although R res is the same. 13 In this study, a scanning system indicated that the LET values varied by 10%-50% for the same R res . R res is a quality index primarily established for a passive system, and it is important to use LET for a spot scanning system.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations